Repeat and Multiple Violent Victimization: Nested Analysis of Men and Women Using the National Violence Against Women Survey (NVAWS), United States, 1994-1996 - Cares, Alison ([Verlag nicht ermittelbar], 2016)
These data are part of NACJD's Fast Track Release and are distributed as they there received from the data depositor. The files have been zipped by NACJD for release, but not checked or processed except of the removal of direct identifiers. Users should refer to the accompany readme file for a brief description of the files available with this collections and consult the investigator(s) if further information is needed. This study was a secondary analysis of National Violence Against Women Survey (NVAWS) data from Violence and Threats of Violence Against Women and Men in the United States, 1994-1996 (ICPSR 2566 - http://doi.org/10.3886/ICPSR02566.v1). This analysis examined the levels and patterns of repeat and multiple violent victimization, and their effects. Distributed here are the codes used to create the datasets and preform the secondary analysis. Please refer to the User Guide, distributed with this study, for more information.